Cardiac involvement in patient-specific induced pluripotent stem cells of myotonic dystrophy type 1: unveiling the impact of voltage-gated sodium channels - Pierre, Marion; Djemai, Mohammed; Chapotte-Baldacci, Charles-Albert; Pouliot, Valérie; Puymirat, Jack; Boutjdir, Mohamed; Chahine, Mohamed (Frontiers in Physiology, 2023)
Myotonic dystrophy type 1 (DM1) is a genetic disorder that causes muscle weakness and myotonia. In DM1 patients, cardiac electrical manifestations include conduction defects and atrial fibrillation. DM1 results in the expansion of a CTG transcribed into CUG-containing transcripts that accumulate in the nucleus as RNA foci and alter the activity of several splicing regulators. The underlying pathological mechanism involves two key RNA-binding proteins (MBNL and CELF) with expanded CUG repeats that sequester MBNL and alter the activity of CELF resulting in spliceopathy and abnormal electrical activity. In the present study, we identified two DM1 patients with heart conduction abnormalities and characterized their hiPSC lines. Two differentiation protocols were used to investigate both the ventricular and the atrial electrophysiological aspects of DM1 and unveil the impact of the mutation on voltage-gated ion channels, electrical activity, and calcium homeostasis in DM1 cardiomyocytes derived from hiPSCs. Our analysis revealed the presence of molecular hallmarks of DM1, including the accumulation of RNA foci and sequestration of MBNL1 in DM1 hiPSC-CMs. We also observed mis-splicing of SCN5A and haploinsufficiency of DMPK. Furthermore, we conducted separate characterizations on atrial and ventricular electrical activity, conduction properties, and calcium homeostasis. Both DM1 cell lines exhibited reduced density of sodium and calcium currents, prolonged action potential duration, slower conduction velocity, and impaired calcium transient propagation in both ventricular and atrial cardiomyocytes. Notably, arrhythmogenic events were recorded, and both ventricular and atrial arrhythmias were observed in the two DM1 cell lines. These findings enhance our comprehension of the molecular mechanisms underlying DM1 and provide valuable insights into the pathophysiology of ventricular and atrial involvement.